Injection of non-reacting gas into production pipelines to ease restart pumping of waxy crude oil - Sulaiman, S.A. (Elsevier B.V., 2017)
Wax deposition in production pipelines causes flow assurance issue due to reduction in flow rate. Gelling of waxy crude oil after subsequent cooling restricts the flow and causes blockage in pipelines, and thus requiring large and costly pumps to restart and regain the steady flow. Nevertheless, the formation of intra-gel voids in the gel was recently reported to ease restart pumping. Further, it is believed that injecting non-reacting gas into the production lines prior to or during shut down could alleviate the restart flow problem and save costs. An experimental work was conducted in order to manipulate the effectiveness of such approach. A flow loop rig was used to simulate the conditions of waxy crude oil in pipelines on seabed and a gas injection system was used to inject nitrogen into the system after crude oil stopped flowing, prior to gelation process. Restart pressure was applied in two modes: instantaneous and gradual pumping. It was observed that maximum restart pressure reductions of 11.48 and 17.44 were achieved when pressure was applied instantaneously and gradually, respectively. It was found that the restart pressure decreased as the gas to oil volume ratio increased due to high slippage effect. In addition, restart pressure under gradual restart approach was observed to be higher than that for instantaneous restart approach. © 2017 Elsevier B.V.